2019
DOI: 10.3390/electronics8080825
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Recognition Method for Electronic Components Based on the Improved YOLO-V3 Network

Abstract: Rapid object recognition in the industrial field is the key to intelligent manufacturing. The research on fast recognition methods based on deep learning was the focus of researchers in recent years, but the balance between detection speed and accuracy was not well solved. In this paper, a fast recognition method for electronic components in a complex background is presented. Firstly, we built the image dataset, including image acquisition, image augmentation, and image labeling. Secondly, a fast recognition m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(36 citation statements)
references
References 26 publications
0
36
0
Order By: Relevance
“…To add to these, one can include the expansion in scale, scope, application, and techniques that provide depth, breadth and multiple perspectives. Recently, AOI algorithms were further enhanced by integrating them with machine learning techniques and deep learning, which at occasions could improve the result and speed of the detection process remarkably [18], [19]. Timm and Barth in [20] suggested that an AOI algorithm must satisfy two major requirements; 100% detection rate and minimum false alarm rate.…”
Section: Optical Inspectionmentioning
confidence: 99%
“…To add to these, one can include the expansion in scale, scope, application, and techniques that provide depth, breadth and multiple perspectives. Recently, AOI algorithms were further enhanced by integrating them with machine learning techniques and deep learning, which at occasions could improve the result and speed of the detection process remarkably [18], [19]. Timm and Barth in [20] suggested that an AOI algorithm must satisfy two major requirements; 100% detection rate and minimum false alarm rate.…”
Section: Optical Inspectionmentioning
confidence: 99%
“…Finally, a feature map of size 52 × 52 and 75 channels are output. Based on this, position regression and classification are performed [31].…”
Section: Res1 Res2 Res8mentioning
confidence: 99%
“…Recall refers to the ability of the model to find all relevant objects; it is the percentage of true positives detected in all ground truths. For binary classification problems, AP measures the performance of the classifier, namely, the area of the P-R curve; AP is introduced to reflect the evaluation effect of the balance between precision and recall [43,44]. Precision and recall are determined by Equations (14) and (15), respectively:…”
Section: Performance Evaluation Indicatorsmentioning
confidence: 99%